Molecular Evidence for the Fitness of Cotton Aphid, Aphis gossypii in Response to Elevated CO2 From the Perspective of Feeding Behavior Analysis - Jiang, Shoulin; Dai, Yang; Lu, Yongqing; Fan, Shuqin; Liu, Yanmin; Bodlah, Muhammad Adnan; Parajulee, Megha N.; Chen, Fajun (Frontiers in Physiology, 2018)
Rising atmospheric CO2 concentration is likely to influence insect–plant interactions. Aphid, as a typical phloem-feeding herbivorous insect, has shown consistently more positive responses in fitness to elevated CO2 concentrations than leaf-chewing insects. But, little is known about the mechanism of this performance. In this study, the foliar soluble constituents of cotton, and the life history of cotton aphid Aphis gossypii, and its mean relative growth rate (MRGR) and feeding behavior were measured, as well as the relative transcript levels of target genes related appetite, salivary proteins, molting hormone and juvenile hormone, to investigate the fitness of A. gossypii in response to elevated CO2. The results indicated that elevated CO2 significantly stimulated the increase of leaf soluble proteins and sucrose of cotton seedlings. Significant increases in adult longevity, lifespan, fecundity and MRGR of A. gossypii were found in elevated CO2 in contrast to ambient CO2. Furthermore, the feeding behavior of A. gossypii was significantly affected by elevated CO2, including significantly shortened the time of stylet penetrating to phloem position and significantly decreased the mean frequency of xylem phase. It is presumed that the fitness of A. gossypii can be enhanced, resulting from the increases in nutrient sources and potentially increased the duration of phloem ingestion under elevated CO2 in contrast to ambient CO2. In addition, the qPCR results also demonstrated that the genes related appetite and salivary proteins significantly up-regulated as well as the gene related molting hormone significantly down-regulated under elevated CO2 in contrast to ambient CO2, this is in accordance with the performance of A. gossypii in response to elevated CO2. So, it is concluded that atmospheric CO2 concentration arising can enhance the fitness of herbivorous aphids via increasing of their ingestion of much more quantity and higher quality of host plant tissues, and simultaneously up-regulating the transcript expression of the genes related appetite and salivary proteins, and then may increase the risk of pest control under the future climate change.